Status Hukum Resolusi Dewan Keamanan PBB Dalam Ranah Hukum Nasional Indonesia - Sheeva Amadea Ratu; Siti Resnawati; Afandi Sitamala (Universitas Serang Raya, 2022)
The United Nations Security Council (UNSC) is one of the six principal organs of the United Nations (UN), charged with ensuring international peace and security, recommending the admission of new UN members to the General Assembly, and approving any changes to the UN Charter. Its powers include establishing peacekeeping operations, enacting international sanctions, and authorizing military action. The UNSC is the only UN body with the authority to give a binding resolution on member states. This research shows that the Security Council as the major of the United Nations has the main task of maintaining international peace and security as mandated in the United Nations Charter. Actions that can be taken by the Security Council are to investigate any dispute that is deemed to be a threat to international peace and security, provide recommendations on method of how to dispute contention, and take action against aggression. In carrying out its functions, the Security Council need to move accordingly to the provisions of the United Nations Charter and applying the international law principles in particular, the principle of peaceful and fair settlement of a dispute. With the existing resolution, each country must adopt every resolution to regulate it in their country include Indonesia.